Breastfeeding-related social media: an online survey of UK mothers' perceptions. (13th November 2019) - Visram, S; Hunter, T
Abstract: Background: Breastfeeding is beneficial for both maternal and infant health, contributing to reduced risk of infections and chronic disease. Despite public health efforts, just 1% of mother-infant dyads in the UK meet international recommendations to breastfeed exclusively until six months. Numerous studies have investigated the influences on suboptimal breastfeeding rates, exposing a myriad of interconnected physiological, psychological and social barriers. Conversely, social support has been shown to be positively associated with breastfeeding duration. The objective of this study was to determine whether and how UK mothers use social media to access breastfeeding advice and support. Methods: An online survey was developed, piloted and distributed via social media using a snowball sampling approach. Responses to closed questions were analysed using SPSS and appropriate statistical tests performed. Free-text responses were analysed manually using thematic analysis. Results: The survey was completed by 1012 mothers, with 992 (98%) reporting use of social media for breastfeeding advice and/or support. Responses revealed a largely positive perception of breastfeeding-related social media. Supportive peer networks and easily accessible information were highlighted as unique features that help to encourage and normalise breastfeeding. Non-university educated mothers were significantly more likely to report this support as "very influential" with regard to how comfortable they felt breastfeeding in public (p = 0.006). Peer-led groups were preferentially used over professional-led groups, particularly by younger women (p = 0.007). Conclusions: There is growing interest in social media as a health platform, particularly in light of recent funding cuts impacting on access to formal support services. By supporting mothers and normalising breastfeeding, social media may help to increase UK breastfeeding rates and reduce health inequalities. Key messages: Many mothers successfully use breastfeeding-related social media for information and support, with a preference for peer-led as opposed to professional-led groups. Future research should explore how public health services can update their practice to better harness these platforms for breastfeeding promotion.